Diagnosing particle acceleration in relativistic jets. Issue Volume 10:Issue S313(2014) (24th March 2015) - Böttcher, Markus; Baring, Matthew G.; Liang, Edison P.; Summerlin, Errol J.; Fu, Wen; Smith, Ian A.; Roustazadeh, Parisa
Abstract: The high-energy emission from blazars and other relativistic jet sources indicates that electrons are accelerated to ultra-relativistic (GeV - TeV) energies in these systems. This paper summarizes recent results from numerical studies of two fundamentally different particle acceleration mechanisms potentially at work in relativistic jets: Magnetic-field generation and relativistic particle acceleration in relativistic shear layers, which are likely to be present in relativistic jets, is studied via Particle-in-Cell (PIC) simulations. Diffusive shock acceleration at relativistic shocks is investigated using Monte-Carlo simulations. The resulting magnetic-field configurations and thermal + non-thermal particle distributions are then used to predict multi-wavelength radiative (synchrotron + Compton) signatures of both acceleration scenarios. In particular, we address how anisotropic shear-layer acceleration may be able to circumvent the well-known Lorentz-factor crisis, and how the self-consistent evaluation of thermal + non-thermal particle populations in diffusive shock acceleration simulations provides tests of the bulk Comptonization model for the Big Blue Bump observed in the SEDs of several blazars.